2009
DOI: 10.1002/hed.21157
|View full text |Cite
|
Sign up to set email alerts
|

Adopting the operating microscope in thyroid surgery: Safety, efficiency, and ergonomics

Abstract: The use of an operating microscope during thyroidectomy is safe with modest increases in surgical time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 7 publications
1
27
1
Order By: Relevance
“…8,9 In the last 40 years there are only a few publications in the literature about the use of microsurgery in thyroid surgery, and all emphasize the concept that microsurgery improves surgical results especially in reinterventions and in lymphadenectomy. 8,[10][11][12][13][14][15][16][17][18] We recently published a paper in which thyroid complications are analysed from a large number of patients using microsurgical technique and optical magnification. 19 In this study we concluded that using the approach proposed can reduce the complications both with regard to hypoparathyroidism and to recurrent nerve paralysis.…”
mentioning
confidence: 99%
“…8,9 In the last 40 years there are only a few publications in the literature about the use of microsurgery in thyroid surgery, and all emphasize the concept that microsurgery improves surgical results especially in reinterventions and in lymphadenectomy. 8,[10][11][12][13][14][15][16][17][18] We recently published a paper in which thyroid complications are analysed from a large number of patients using microsurgical technique and optical magnification. 19 In this study we concluded that using the approach proposed can reduce the complications both with regard to hypoparathyroidism and to recurrent nerve paralysis.…”
mentioning
confidence: 99%
“…Microscope-assisted thyroidectomy has also been championed for its ergonomic benefits to the surgeon. The operating microscope has been proposed as a method to maintain an upright posture with neutral cervical position during thyroid surgery, so reducing occupational musculoskeletal risk (18). The authors, though, noted a significant increase in operating time especially in case of lateral neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of surgery appears to be longer with the use of an intra-operative microscope. In a recent study of 116 thyroidectomies with and without the use of an intraoperative microscope, Davidson and colleagues reported a significant increase (P<0.001) of 30 minutes in procedures with the use of an intra-operative microscope (14). The authors attributed the increased operative time to the time used to adjust the microscope for visualization of the surgical field (14).…”
Section: Discussionmentioning
confidence: 99%